ANALISIS KETIDAKJUJURAN AKADEMIK JENJANG PENDIDIKAN TINGGI DI TIMOR-LESTE - Sandra H.M.S Pereira; Indah Widiastuti; Ngatou Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
The phenomenon of dishonesty occurs a lot in the academic field, one of which is plagiarism and cheating which are often encountered in universities in the process of learning and research. Academic dishonesty at the tertiary level in Timor-Leste is considered to affect the integrity of graduates when entering the workforce. The purpose of this study is to analyze indicators of academic dishonesty, causes of academic dishonesty, and appropriate solutions to overcome academic dishonesty of university students in Timor-Leste class of 2020-2022. This research is a positivistic quantitative, descriptive research. The research was conducted using a Google form. The subjects of the study were 59 university students in the Timor-Leste class of 2020-2022. The data collection technique is by using questionnaire methods and questionnaire instruments. Validity and reliability of data using the help of data processing software. Data analysis uses descriptive statistical analysis technique. The results showed that the indicators of academic dishonesty of Higher Education Students in the Timor-Leste class of 2020-2022 were Working together with friends during the exam, Allowed other students to see answers during quizzes or exams, Asking exam questions to other students who had done exams before, Seeing cases of cheating in class and not reporting it to the supervisor. The cause of academic dishonesty is that the questions given are very difficult and students consider working together during exams a form of solidarity. The solution to overcome academic dishonesty is that there is a reprimand when committing academic cheating, supervisors are firm in addressing academic dishonesty, and there are severe penalties when caught cheating.